Increased serum interleukin 22 levels in patients with axial spondyloarthritis. (2nd January 2023) - Slouma, Maroua; Kharrat, Lobna; Tezegdenti, Aymen; Metoui, Leila; Dhahri, Rim; Ghazouani, Ezzeddine; Cheour, Elhem; Gharsallah, Imen; Louzir, Bassem
ABSTRACT: Objectives: The role of IL-22 in radiographic axial spondyloarthritis is not fully elucidated. Thus, there is a need for new insights into this cytokine in this disease. We aimed to compare interleukin (IL)-22 level between spondyloarthritis, nonspecific-low back pain patients, and pain-free controls, and to evaluate associations between this cytokine and spondyloarthritis characteristics. Methods: We conducted a case-control study including 62 patients with radiographic axial spondyloarthritis (G1), 46 with nonspecific low back pain (G2), and 42 healthy volunteers (G3). IL-22 was measured using Enzyme-linked immunosorbent assay. We evaluate disease activity and structural damage of spondyloarthritis. Results: IL-22 level was higher in G1 than in G2 and G3 (38±40 versus14.42±8.17 versus14.3±18.67 pg/mL, p<0.01). IL-22 discriminated patients in G1 from G2 with a cutoff of 22.28pg/mL (Sensitivity: 62.9%, Specificity: 97.8%, area under the curve (AUC): 0.808). IL-22 cutoff of 19.27pg/mL discriminated patients in G1 from G3 (Sensitivity: 67%, Specificity: 94.3%, AUC: 0.855). No associations were found between IL-22 levels and disease activity and structural damage.            Conclusions: Our study showed that IL-22 level was higher in radiographic axial spondyloarthritis patients compared to controls. It was also able to differentiate G1 patients from G2 and G3. This finding suggests that the IL-22 pathway showed to play a pathological role in spondyloarthritis.